1992
DOI: 10.1002/app.1992.070440617
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of model latices for the study of coalescence mechanisms

Abstract: SYNOPSISThis work describes the synthesis of model latices devoted to the study of the influence of pafticle-water and particle-air interfacial energies on coalescence mechanisms. Core-shell particles with the same diameter ( N 2600 A ) and narrow size distributions were prepared.The core is a poly( styrene-co-butyl acrylate) (60/40 wt % ) copolymer; it represents 90% of the volume of the particle. The shell is a poly(St-BuA-methacrylic acid) terpolymer with 10, 15, or 25 wt % MAA. The St-BuA weight ratio in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…Indeed, it has been shown that the film formation process is highly dependent upon temperature and water evaporation rate. 4 For instance, when the water evaporation rate is decreased and the drying temperature kept constant, the film-forming ability is enhanced, whereas increasing the drying temperature and keeping a constant water evaporation rate increases the film-forming ability. Therefore, MFFT measurements make it difficult to analyze and compare the film-forming ability of latex blends because different MFFT indicates simultaneously a different water evaporation rate and a different polymer chain mobility.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, it has been shown that the film formation process is highly dependent upon temperature and water evaporation rate. 4 For instance, when the water evaporation rate is decreased and the drying temperature kept constant, the film-forming ability is enhanced, whereas increasing the drying temperature and keeping a constant water evaporation rate increases the film-forming ability. Therefore, MFFT measurements make it difficult to analyze and compare the film-forming ability of latex blends because different MFFT indicates simultaneously a different water evaporation rate and a different polymer chain mobility.…”
Section: Resultsmentioning
confidence: 97%
“…Dobler et al 4 preof the biphasic film. Mullins and Tobin 12 quantisented clear evidence that by decreasing the wafied the strain amplification phenomenon by modter evaporation rate, one increases the film-formifying the Mooney-Rivlin equation [eq.…”
Section: Film-forming Abilitymentioning
confidence: 98%
“…[1][2][3] Any voids or defects in the film structure will result in a higher diffusion rate of water through the film.…”
Section: Introductionmentioning
confidence: 99%
“…The current model for latex film formation [1][2][3] is that it occurs in four steps: the concentration of the latex, the sintering or deformation of the particle, the coalescence and rupture of interparticle membranes, and the interdiffusion of polymer chains to form a coherent film (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Seed particles can be prepared either in a separate step, or formed in situ during one-stage polymerization. [6][7][8][9][10][11] The resulting particles are commonly referred to as "core-shell" particles, implying a particle structure with the initially polymerized polymer located in the centre of the particle and the later-formed polymer becoming incorporated into the outer shell layer. [12][13][14][15] Recently, micron-sized polymer composites particles with core-shell morphology have widely been used as the impact modifier for plastics, compatibilizer for polymer blends, and adhesives.…”
Section: Introductionmentioning
confidence: 99%